Clinicopathological characteristics of the CD8 + T lymphocytes infiltration and its mechanism in distinct molecular subtype of medulloblastoma - Chai, Xiaodong; Sun, Ziwen; Li, Haishuang; Zhu, Liangyi; Liu, Xiaodan; Liu, Yantao; Pei, Fei; Chang, Qing (Beijing da xue xue bao. Journal of Peking University. Yi xue ban, 2024)
To investigate the characteristics of the CD8 T cells infiltration from the 4 subtypes in medulloblastoma (MB), to analyze the relationship between CD8 T cells infiltration and prognosis, to study the function of C-X-C motif chemokine ligand 11 (CXCL11) and its receptor in CD8 T cells infiltration into tumors and to explore the potential mechanism, and to provide the necessary clinicopathological basis for exploring the immunotherapy of MB. In the study, 48 clinical MB samples (12 cases in each of 4 subtypes) were selected from the multiple medical center from 2012 to 2019. The transcriptomics analysis for the tumor of 48 clinical samples was conducted on the NanoString PanCancer IO360 Panel (NanoString Technologies). Immunohistochemistry (IHC) staining of formalin-fixed, paraffin-embedded sections from MB was carried out using CD8 primary antibody to analyze diffe-rential quantities of CD8 T cells in the MB four subtypes. Through bioinformatics analysis, the relationship between CD8 T cells infiltration and